The 3-D animation of radiation concept using augmented reality technology - Bakri, F; Kencana, H P; Permana, H; Muliyati, D (Journal of physics. Conference series, 2019)
Radiation concept in Nuclear subject in Physics Learning include some devices, such as Geiger Muller counter, Wilson cloud chamber, scintillation detector. This research aims to visualize the radiation concept from that device using augmented reality technology. The result shows the 3-D animation can: describe the mechanism of the Geiger Muller counter detector to detect radiation; describe the mechanism of Wilsons fog chamber detects radiation; and describe the mechanism of the scintillation detector tool to detect radiation. All the markers developed to get a decent value to be used as a medium for learning physics about radiation concept.